Revisiting the prosecutor v Dominic Ongwen : towards a possible complementarity between traditional justice and the international criminal court? - Killander, Magnus (University of Pretoria, 2023)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa)- University of Pretoria, 2023.